Evaluating the Potential of Cultural Diplomacy as “A Weapon of Enduring Peace in the Gulf Region” - Shamsi, Zia Ul Haque (Pakistan Journal of Humanities and Social Sciences, 2023)
Diplomacy, as a tool to further the state’s interests, has endless possibilities; it has a reason in all facets of the state because it works without the fear of failure. Diplomacy has a role in every domain of the state: external relations, governance, commerce and trade, economic development, lawfare, culture, and sports. Diplomacy can make things happen, because it may start from an impossible objective, but remains operative until it has made it possible or at least probable. Cultural diplomacy may effectively promote a country’s soft image if deployed intelligently and passionately. Because, it is one of the oldest methods of diplomacy, where every citizen is a diplomat when he/she interacts with people of other cultures. Since ancient times, traders, travelers, students, and nomads, were inherently the ambassadors of the state. Cultural diplomacy has a wide canvas and hence is an effective communicator. From cuisines to dresses, language to rituals, tourism to trade, and music to dramas. Through effective cultural diplomacy, one can enter into the hearts and minds of the people beyond borders. It has a popular appeal among the people within and without. The colonial masters during the period of colonialism effectively promoted their culture, sometimes under the banner of cultural diplomacy, and at times through the use of force. In contemporary times, each of the Gulf states is effectively exploiting its cultural strengths to attract tourism, investment, and residents. While KSA is thriving on its ideological culture, Qatar is prevalent as a regional hub of sports. UAE is successfully interpolating modernity, and Oman is making the best use of its topographical advantage to promote its culture. This paper aims to highlight the significance of cultural diplomacy as a soft power and evaluate its potential as a weapon of enduring peace and stability in the Gulf sub-region of otherwise conflict-ridden Middle East. To maintain originality and objectivity, inductive reasoning with qualitative analysis is deployed in this research. Additionally, a new strategic appraisal tool 1 SIMPLE has been developed especially for this paper.